Diverse immunopathological manifestations and immunogenomic predispositions in COVID-19: summarizing the evidence - Deb, Shramana; Mondal, Ritwick; Lahiri, Durjoy; Ganguly, Upasana; Shome, Gourav (International Journal of Research in Medical Sciences, 2022)
The COVID-19 pandemic has caused immense damage to most nations of the world, both in terms of loss of human lives, as well as, socio-economic attributes. The immunopathogenesis of the responsible pathogen, SARS-CoV-2, has been a focal point and researchers have succeeded in deciphering the multi-organ tropism of the virus along with its different routes of infection. The hallmark feature of the SARS-CoV-2 disease pathogenesis is the high rates of transmission and the susceptibility of a vulnerable group with systemic co-morbidities. Also, genetic components of the host, as well as mutant variants of the virus have further complicated the development of appropriate treatment strategies and preventive measures. The virus is aptly able to modulate the host immune system and mediate immune-dysregulation in terms of cytokine or chemokine production leading to a heightened inflammatory response. In the current review, we have summarized the present research on SARS-CoV-2 from the angles of host genetic polymorphism, genetic variants of the virus, and how these affect the high transmission, disease susceptibility, and tissue tropism in multiple organs of the human body.